2013
DOI: 10.2528/pier12101604
|View full text |Cite
|
Sign up to set email alerts
|

System Development of Microwave Induced Thermo-Acoustic Tomography and Experiments on Breast Tumor

Abstract: Abstract-Microwave induced thermo-acoustic tomography (MI-TAT) has become a keen research topic in recent years due to its great potential in early breast cancer detection. A secure and accurate MI-TAT system has been established. Some experiments have been made to demonstrate the performance of the MITAT system. Based on an experiment using phantom, some quantitative features of the system have been obtained. Some imaging experiments with real human breast cancer tissues are performed to demonstrate its effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…All the scanning procedures with 1.8 • step can be finished within two minutes. More details about the system can be found in [34]- [36]. …”
Section: Mitat Model and Real Imaging Systemmentioning
confidence: 99%
“…All the scanning procedures with 1.8 • step can be finished within two minutes. More details about the system can be found in [34]- [36]. …”
Section: Mitat Model and Real Imaging Systemmentioning
confidence: 99%
“…Fig. 4(b) shows a sketch map of the MITAT system which has been illustrated in [20,21]. The pulse width of the microwave generator is adjustable.…”
Section: Methodsmentioning
confidence: 99%
“…The imaging depth is affected by the penetration depth and the intensity of pulsed microwave, and the surface area is affected by the microwave radiation region. 18 For previously used frequencies of 3 and 6 GHz in TAI systems, the penetration depth of high-water content tissues such as skin and muscles are estimated to be only 3.2 and 1.2 cm, respectively, which are not adequate in applications requiring large FOV. Previous studies demonstrated that sufficient penetration depth can be achieved by using microwave operating at 434 MHz.…”
Section: Introductionmentioning
confidence: 99%